Integrating Energy and Environmental Management in Wood Furniture Industry - Dušan Gordić; Milun Babić; Dubravka Jelić; Davor Konćalović; Vladimir Vukašinović (The Scientific World Journal)
As energy costs continue to rise, industrial plants (even those of energy nonintensive industries such as furniture industry) need effective way to reduce the amount of energy they consume. Besides, there are a number of economic and environmental reasons why a company should consider environmental management initiatives. This paper provides a detailed guideline for implementing joint energy and environmental management system in wood furniture industrial company. It covers in detail all essential aspects of the system: initial system assessment, organization, policy development, energy and environmental auditing, action plan development, system promotion, checking system performance, and management review.